Family members' experiences of psychosocial support in palliative care inpatient units: A descriptive qualitative study - Anu, Soikkeli-Jalonen; Kaisa, Mishina; Virtanen, Heli; Charalambous, Andreas; Haavisto, Elina (My University, 2022)
Purpose The support for family members (FMs) during a patient's palliative hospital care has been rarely studied, creating a gap in how FMs can be better supported. Psychosocial support answers widely to FMs' needs. Therefore, this study aims to describe FMs’ experiences of psychosocial support in specialist palliative care inpatient units from the perspective of the FMs themselves. Methods A qualitative descriptive study with individual semi-structured interviews and inductive content analysis was conducted. Data were collected in four specialist palliative care inpatient units in two large hospital districts in Finland. The 32-item checklist Consolidated Criteria for Reporting Qualitative Studies was used to ensure detailed reporting. Results A total of 19 FMs of cancer patients receiving palliative care participated in the study. Their experiences of psychosocial support focused on Support FMs hoped for, Support practices in the care unit, and Informational support for FMs. Conclusions According to FMs' experiences, support focusing particularly on the FMs, safe quality patient care, proper access to information regarding the patient's care and condition, and genuine encounters with HCPs were the aspects that seemed to be the most important to the FMs. Systematic provision of support and information should be a routine model in palliative care. Additionally, a care environment that promotes FMs' presence, participation, and family-centred care is essential in FMs' support and should be considered when developing family involvement in palliative care. Furthermore, the importance of FMs receiving sufficient information, and FMs' dependence on HCPs to share the needed information, should be acknowledged. Hence, more attention should be paid to successful information sharing between the HCPs and FMs in palliative hospital care.
Keywords: Family; Inpatients; Qualitative study; Palliative care; Psychosocial support; Caregivers